Metal fixing material
Patent Information
- Application Number
- JP2021079125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-05-07
AI Technical Summary
Existing cellulose derivatives used for recovering valuable metals also adsorb alkali and alkaline earth metals, leading to non-selective recovery, and are water-soluble, making it difficult to recover adsorbed metals efficiently.
A metal fixing material comprising a cellulose derivative with dithiocarbamate groups, combined with a cationic coagulant and an anionic polymer flocculant, selectively adsorbs valuable and harmful metals, forming flocs that can be easily separated and recovered.
The material achieves selective and efficient recovery of valuable metals and harmful metals by forming flocs that can be easily filtered and reduced in volume through heat treatment, reducing disposal costs.
Smart Images

Figure 00000010_0000 
Figure 00000026_0000
Abstract
Description
Technical Field
[0001] The present disclosure relates to a metal fixing material and a method for fixing a metal using the metal fixing material.
Background Art
[0002] Arsenic is known as an element harmful to the human body. Among inorganic arsenics, As(III) in particular exhibits strong toxicity. As(III) in wastewater is coagulated and precipitated by a coagulant and separated from the liquid (coagulation precipitation method). However, since As(III) dissolves in the liquid as a low-molecular-weight uncharged species in a wide pH range, the problem is that the removal efficiency is low. In addition, a large amount of coagulant is required to coagulate and precipitate As(III), and as a result, a large amount of sludge is generated. Therefore, it has also been a problem that large-scale equipment and sludge treatment are costly.
[0003] In recent years, valuable metals such as ruthenium, cobalt, rhodium, iridium, nickel, palladium, platinum, copper, silver, and gold have been widely used in electronic materials, electronic components, industrial catalysts, metal plating, etc. In the medical field, platinum is used as an anticancer agent, and palladium is used for dental treatment.
[0004] In Japan, although a large amount of valuable metals are consumed, most of them depend on imports. Therefore, from the perspective of effective use of resources, it is desired to recover and reuse valuable metals contained in factory wastewater and waste.
[0005] Patent Document 1 describes that when iminodiacetic acid or dialkylamine is bonded to cellulose having a crystallinity of 70% or less, a large number of functional groups capable of forming a chelate with a valuable metal can be introduced, and according to the cellulose derivative thus obtained, valuable metals can be efficiently recovered.
Prior Art Documents
Patent Documents
[0006] [Patent Document 1] Japanese Patent Publication No. 2009-247981 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] However, the cellulose derivative readily forms salts with alkali metals and alkaline earth metals. As a result, the cellulose derivative adsorbs alkali metals and alkaline earth metals, which are abundant in nature, along with the valuable metal, making it impossible to selectively recover the valuable metal.
[0008] Furthermore, the inventors have discovered that cellulose derivatives into which a dithiocarbamate group, which corresponds to a soft base according to the HSAB rule, is introduced, do not adsorb alkali metals or alkaline earth metals, which correspond to hard acids according to the HSAB rule, but selectively adsorb valuable metals and harmful metals, which correspond to soft acids or intermediate acids.
[0009] However, because cellulose derivatives into which dithiocarbamate groups have been introduced are readily soluble in water, it was difficult to recover the cellulose derivatives from which valuable or harmful metals had been adsorbed.
[0010] Therefore, the purpose of this disclosure is to provide a metal fixing material that is useful for selectively and efficiently recovering valuable metals and harmful metals in a simple manner. Another object of this disclosure is to provide a method for fixing metal using the metal fastener. [Means for solving the problem]
[0011] As a result of diligent research to solve the above problems, the present inventors have found that when a cellulose derivative to which a dithiocarbamate group corresponding to a soft base in the HSAB rule has been introduced is subjected to aqueous solution, and cations selectively adsorb valuable metals or harmful metals corresponding to a soft acid or intermediate acid in the HSAB rule, and then a specific coagulant and polymer flocculant are added, the cellulose derivative quickly forms flocs (clumps), and can be easily separated from the aqueous solution by simple methods such as filtration. This disclosure is completed based on these findings.
[0012] In other words, this disclosure provides a metal fixing material consisting of a combination of the following components A, B, and C. Component A: A metal adsorbent containing a cellulose derivative having repeating units represented by the following formula (I). [ka] [In the formula, R a These are the same or different hydrogen atoms or groups represented by the following formula (a). Note that all R groups contained in cellulose derivatives are included. a Of these, at least one is a group represented by the following formula (a). [ka] (In the formula, ring Z represents a heterocycle containing a nitrogen atom as a heteroatom, R 1 represents a single bond or an alkylene group with 1 to 10 carbon atoms. 4 R 2 (These represent identical or different alkyl groups with 1 to 10 carbon atoms.) Component B: Coagulant Component C: Polymer flocculant
[0013] This disclosure also provides a metal fixing material wherein the coagulant is a cationic coagulant.
[0014] This disclosure also provides a metal fixing material wherein the polymer flocculant is an anionic polymer flocculant.
[0015] This disclosure also provides a metal fixing material wherein the anionic polymer flocculant is a polymer containing monomer units derived from anionic monomers, and the proportion of monomer units derived from the anionic monomers in the total monomer units constituting the polymer is 30% by weight or more.
[0016] This disclosure also provides a metal fixing material containing 0.1 to 10 parts by weight of component B with respect to 1 part by weight of component A.
[0017] This disclosure also provides a metal fixing material containing 0.1 to 10 parts by weight of component C with respect to 1 part by weight of component A.
[0018] The present disclosure also provides a metal fixing material having a ratio of the content of component B to component C (B / C; weight ratio) of 20 / 80 to 80 / 20.
[0019] This disclosure also provides the metal fixing material which is a fixing material for the following metals. Metals: Metals whose cations fall under the category of soft acids or intermediate acids in the HSAB rules.
[0020] The disclosure also provides a metal fixing material which is a fixing material of at least one metal selected from titanium, vanadium, manganese, iron, cobalt, nickel, copper, zinc, gallium, arsenic, selenium, cadmium, indium, lead, bismuth, ruthenium, rhodium, iridium, palladium, platinum, silver, and gold.
[0021] This disclosure also provides a metal fixation method comprising the steps of adding component A to an aqueous solution containing a dissolved metal, and then adding components B and C to form a floc containing the metal, component A, component B, and component C. Component A: A metal adsorbent containing a cellulose derivative having repeating units represented by the following formula (I). [ka] [In the formula, R aThese are the same or different hydrogen atoms or groups represented by the following formula (a). Note that all R groups contained in cellulose derivatives are included. a Of these, at least one is a group represented by the following formula (a). [ka] (In the formula, ring Z represents a heterocycle containing a nitrogen atom as a heteroatom, R 1 represents a single bond or an alkylene group with 1 to 10 carbon atoms. 4 R 2 (These represent identical or different alkyl groups with 1 to 10 carbon atoms.) Component B: Coagulant Component C: Polymer flocculant [Effects of the Invention]
[0022] The metal fixing material of this disclosure consists of a combination of components A, B, and C. Component A has the property that its cations readily adsorb metals corresponding to soft acids or intermediate acids according to the HSAB rule (e.g., valuable metals and hazardous metals), while being less likely to adsorb metals corresponding to hard acids (e.g., alkali metals and alkaline earth metals). Furthermore, when components B and C are added to a liquid containing component A on which the metal has been adsorbed, component A, on which the metal has been adsorbed, quickly forms flocs together with components B and C, and can be separated from the liquid by simple methods such as filtration. In addition, the flocs separated from the liquid can be significantly reduced in volume by heat treatment.
[0023] Therefore, by using the aforementioned metal fixing material, harmful metals can be efficiently and selectively fixed into the flocs from water contaminated with harmful metals, and the flocs can be easily recovered by filtration or other means. Furthermore, by reducing the volume of the recovered flocs by heat treatment, disposal costs such as landfill can be significantly reduced.
[0024] Furthermore, by using the aforementioned metal fixing material, valuable metals can be selectively and efficiently fixed into the flocs from factory wastewater and waste, and the flocs can be easily recovered by filtration or other means. In addition, by subjecting the recovered flocs to incineration treatment, the valuable metals fixed within the flocs can be easily recovered and reused. [Brief explanation of the drawing]
[0025] [Figure 1] This figure shows the IR spectrum of cellulose derivative 1 obtained in Preparation Example 1. [Modes for carrying out the invention]
[0026] [Metal fixing material] The metal fastener of this disclosure consists of a combination of the following components A, B, and C. Component A: Metal adsorbent Component B: Coagulant Component C: Polymer flocculant
[0027] Component A has excellent adsorption capacity for valuable and harmful metals that fall under the category of soft or intermediate acids in the HSAB rules. On the other hand, its adsorption capacity for metals that fall under the category of hard acids in the HSAB rules is low.
[0028] Therefore, the metal fixing material allows for the selective and efficient fixation of cations from aqueous solutions containing various metals (for example, industrial wastewater, mine wastewater, hot spring water, etc.), particularly valuable and harmful metals that fall under the category of soft acids or intermediate acids in the HSAB Law.
[0029] The fixation rate of cations corresponding to soft acids or intermediate acids in the HSAB rule (for example, metals selected from cobalt, selenium, iridium, nickel, palladium, platinum, copper, zinc, silver, and gold) is, for example, 85% or more, preferably 90% or more, and particularly preferably 95% or more.
[0030] The fixation rate of harmful metals (such as metals selected from arsenic, cadmium, and lead) whose cations correspond to soft acids or intermediate acids in the HSAB principle is, for example, 85% or more, preferably 90% or more, particularly preferably 95% or more.
[0031] The fixation rate of metals (such as alkali metals and alkaline earth metals) whose cations correspond to hard acids in the HSAB principle by the metal fixing material is, for example, 10% or less, preferably 5% or less, particularly preferably 1% or less, and most preferably 0.1% or less.
[0032] The fixation rate of base metals (particularly iron, aluminum, and manganese) by the metal fixing material is, for example, 60% or less, preferably 50% or less, more preferably 45% or less, still more preferably 30% or less, particularly preferably 20% or less, most preferably 10% or less, and especially preferably 5% or less.
[0033] In addition, in the present disclosure, the fixation rate of a metal is the fixation rate when 10 mg of component A is added to 10 mL of an aqueous solution (pH 7) with a metal element concentration of 2 mM at 25°C, stirred at 200 rpm for 20 minutes, then 20 mg of component B and 10 mg of component C are added, and stirred at 200 rpm for 60 minutes, and can be calculated by the method described in the examples.
[0034] (Component A) The component A is a metal adsorbent and at least contains a cellulose derivative having a repeating unit represented by the following formula (I) (hereinafter, may be referred to as "cellulose derivative (I)").
Chemical formula
Chemical formula
[0035] Ring Z is a heterocycle containing a nitrogen atom as a heteroatom. Ring Z may also contain heteroatoms other than nitrogen.
[0036] Among the ring Z components, a heterocycle containing only a nitrogen atom as a heteroatom (particularly a non-aromatic heterocycle) is preferred. Furthermore, ring Z is, for example, a 3- to 10-membered ring, with a 4- to 8-membered ring being preferred, and a 4- to 6-membered ring being particularly preferred.
[0037] Examples of ring Z include five-membered rings such as pyrrolidine rings; and six-membered rings such as piperidine rings and piperazine rings.
[0038] R 1 Examples of alkylene groups having 1 to 10 carbon atoms include linear or branched alkylene groups such as methylene group, methylmethylene group, dimethylmethylene group, ethylene group, 2-methylethylene group, 1,2-dimethylethylene group, propylene group, trimethylene group, and 2-methyl-trimethylene group.
[0039] R 1 Preferably, this is a single bond or an alkylene group having 1 to 2 carbon atoms.
[0040] R 2 Examples of C1-C10 alkyl groups in this context include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, s-butyl, t-butyl, and pentyl groups.
[0041] R 2 Preferably, it is an alkyl group having 1 to 3 carbon atoms.
[0042] Among the groups represented by formula (a), the group represented by formula (a-1) or formula (a-2) below is preferred. In the following formula, R 2 The same applies as above. [ka]
[0043] Among the groups represented by formula (a), the group represented by the following formula (a-1') or the group represented by the following formula (a-2') is preferred. In the following formula, R 1 The same applies as above. [ka]
[0044] The overall average degree of substitution of the group represented by formula (a) (preferably the group represented by formula (a-1), (a-2), (a-1'), or (a-2')) (the average value of the degree of substitution of the hydrogen atoms of the hydroxyl groups at positions 2, 3, and 6 of the glucose unit constituting cellulose to the said group) is, for example, 0.1 to 3.0, preferably 1.0 to 3.0, and particularly preferably 2.0 to 3.0. It is preferable that the cellulose derivative (I) contains the said group within the said range in order to exhibit excellent metal adsorption capacity.
[0045] The weight-average molecular weight of the cellulose derivative (I) is, for example, 5,000 or more, preferably 10,000 or more, and particularly preferably 50,000 or more. The upper limit of the weight-average molecular weight is, for example, 5 million, preferably 2 million, particularly preferably 1 million, and most preferably 500,000.
[0046] The cellulose derivative (I) has a group represented by formula (a) above, and the group contains a dithiocarbamate group which corresponds to a soft base in the HSAB rule. Therefore, it has excellent adsorption capacity for metal ions (for example, at least one metal selected from titanium, vanadium, manganese, iron, cobalt, nickel, copper, zinc, selenium, gallium, arsenic, cadmium, indium, lead, bismuth, ruthenium, rhodium, iridium, palladium, platinum, silver, and gold) which correspond to soft acids or intermediate acids in the HSAB rule. In other words, the cellulose derivative (I) acts as an adsorbent for metals whose cations correspond to soft acids or intermediate acids in the HSAB rule.
[0047] The (saturated) adsorption capacity of the cellulose derivative (I) for metals whose cations correspond to soft acids or intermediate acids in the HSAB rule is, for example, 1 mol / kg or more, preferably 2 mol / kg or more, more preferably 2.5 mol / kg or more, even more preferably 3 mol / kg or more, particularly preferably 3.5 mol / kg or more, and most preferably 5 mol / kg or more.
[0048] The (saturated) adsorption capacity of the cellulose derivative (I) for the harmful metal is, for example, 0.2 mol / kg or more, preferably 0.3 mol / kg or more, more preferably 0.5 mol / kg or more, even more preferably 0.6 mol / kg or more, particularly preferably 1 mol / kg or more, and most preferably 2 mol / kg or more.
[0049] The arsenic adsorption capacity is, for example, 0.2 mol / kg or more, preferably 0.5 mol / kg or more, and more preferably 1 mol / kg or more.
[0050] The cellulose derivative (I) has low adsorption capacity for metals whose cations correspond to hard acids in the HSAB rule (especially alkali metals, alkaline earth metals, and base metals).
[0051] The (saturated) adsorption capacity of cations for metals that correspond to hard acids in the HSAB rule (e.g., alkali metals such as sodium and potassium; alkaline earth metals such as magnesium, calcium, strontium, and barium; base metals such as iron, aluminum, and manganese) is, for example, 2.0 mol / kg or less, more preferably 1.6 mol / kg or less, even more preferably 0.8 mol / kg or less, particularly preferably 0.4 mol / kg or less, most preferably 0.1 mol / kg or less, and especially preferably 0.01 mol / kg or less.
[0052] Furthermore, the cellulose derivative (I) exhibits excellent storage stability because the strain on ring Z (e.g., a heterocycle such as piperidine or pyrrolidine) in the group represented by formula (a) suppresses proton transfer to the nitrogen atom, which is the starting point for the decomposition of the dithiocarbamic acid group. For example, even after subjecting the cellulose derivative (I) to a test in which it is left to stand in an air atmosphere at 40°C for two weeks, it retains the same high metal adsorption capacity as before the test. The retention rate of the metal adsorption capacity is, for example, 95% or more.
[0053] Component A may contain other components besides cellulose derivative (I), but the proportion of cellulose derivative (I) is, for example, 50% by weight or more, preferably 60% by weight or more, particularly preferably 70% by weight or more, most preferably 80% by weight or more, and especially preferably 90% by weight or more, of the total amount of component A. If the proportion of cellulose derivative (I) falls below the above range, it tends to become difficult to efficiently and selectively adsorb metals. In addition, storage stability tends to decrease.
[0054] There are no particular restrictions on the dosage form of component A as long as it is effective, and examples include powder, pellets, threads, and nonwoven fabrics.
[0055] Cellulose derivative (I) can be produced, for example, by the following steps [1][2][3]. [ka]
[0056] R in the above formula 1 , R 2 , ring Z, R a The same applies as above.
[0057] R in the above formula 0 This indicates a monovalent hydrocarbon group or a monovalent heterocyclic group.
[0058] The hydrocarbon groups include aliphatic hydrocarbon groups, alicyclic hydrocarbon groups, aromatic hydrocarbon groups, and groups formed by combining these.
[0059] Examples of aliphatic hydrocarbon groups include alkyl groups having 1 to 10 carbon atoms (particularly preferably 1 to 3 carbon atoms), such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, s-butyl, t-butyl, pentyl, hexyl, and decyl groups; and alkenyl groups having 2 to 10 carbon atoms (particularly preferably 2 to 3 carbon atoms), such as vinyl, allyl, and 1-butenyl groups.
[0060] Examples of alicyclic hydrocarbon groups include cycloalkyl groups with 3 to 10 members (particularly preferably 5 to 8 members) such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cyclooctyl groups; cycloalkenyl groups with 3 to 15 members (particularly preferably 5 to 8 members) such as cyclopentenyl and cyclohexenyl groups; perhydronaphthalene-1-yl, norbornyl, adamantyl, and tricyclo[5.2.1.0 2,6 ] Decane-8-yl group, tetracyclo[4.4.0.1 2,5 .1 7,10 Examples include bridged cyclic hydrocarbon groups such as dodecane-3-yl groups.
[0061] Examples of aromatic hydrocarbon groups include aryl groups having 6 to 20 carbon atoms, such as phenyl groups, naphthyl groups, and anthracenyl groups. Furthermore, the aromatic ring constituting the aromatic hydrocarbon group may be fused with another ring (e.g., an alicyclic ring) to form a fused ring. Examples of groups containing such fused rings include fluorene groups.
[0062] The aforementioned heterocyclic group is a group obtained by removing one hydrogen atom from the structural formula of a heterocycle. The aforementioned heterocycle includes aromatic heterocycles and non-aromatic heterocycles. Examples of such heterocycles include 3- to 10-membered rings (preferably 4- to 6-membered rings) having a carbon atom and at least one heteroatom (e.g., oxygen atom, sulfur atom, nitrogen atom, etc.) as atoms constituting the ring, and fused rings thereof. Specifically, heterocycles containing an oxygen atom as a heteroatom (e.g., 3-membered rings such as oxirane rings; 4-membered rings such as oxetane rings; 5-membered rings such as furan rings, tetrahydrofuran rings, oxazole rings, isoxazole rings, γ-butyrolactone rings; 6-membered rings such as 4-oxo-4H-pyran rings, tetrahydropyran rings, morpholine rings; fused rings such as benzofuran rings, isobenzofuran rings, 4-oxo-4H-chromene rings, chroman rings, isochroman rings; 3-oxatricyclo[4.3.1.1 4,8 ]Undecane-2-one ring, 3-oxatricyclo[4.2.1.0 4,8 Examples include bridged rings such as nonane-2-one rings, heterocycles containing a sulfur atom as a heteroatom (e.g., five-membered rings such as thiophene rings, thiazole rings, isothiazole rings, and thiadiazole rings; six-membered rings such as 4-oxo-4H-thiopyran rings; condensed rings such as benzothiophene rings, etc.), and heterocycles containing a nitrogen atom as a heteroatom (e.g., five-membered rings such as pyrrole rings, pyrrolidine rings, pyrazole rings, imidazole rings, and triazole rings; six-membered rings such as isocyanuric rings, pyridine rings, pyridazine rings, pyrimidine rings, pyrazine rings, piperidine rings, and piperazine rings; condensed rings such as indole rings, indoline rings, quinoline rings, acridine rings, naphthyridine rings, quinazoline rings, and purine rings, etc.).
[0063] The hydrocarbon group or heterocyclic group may have various substituents [for example, halogen atoms, oxo groups, hydroxyl groups, substituted oxy groups (for example, alkoxy groups, aryloxy groups, aralkyloxy groups, acyloxy groups, etc.), carboxyl groups, substituted oxycarbonyl groups (for example, alkoxycarbonyl groups, aryloxycarbonyl groups, aralkyloxycarbonyl groups, etc.), substituted or unsubstituted carbamoyl groups, cyano groups, nitro groups, substituted or unsubstituted amino groups, sulfo groups, etc.].
[0064] R in the above formula b These are the same or different hydrogen atoms or the group represented by formula (b) above. Note that all R contained in cellulose derivative (II) b Of these, at least one is a group represented by formula (b) above.
[0065] R in the above formula c These are the same or different hydrogen atoms or the group represented by formula (c) above. Note that all R contained in cellulose derivative (III) c Of these, at least one is a group represented by formula (c) above. Furthermore, the group represented by formula (c) may form a salt.
[0066] Step [1] is a step in which the hydroxyl group of cellulose (1-1) (= a compound having repeating units represented by the above formula (1-1)) is reacted with the compound represented by the above formula (2) (hereinafter sometimes referred to as "imino acid (2)").
[0067] Imino acid (2) is an imino acid in which the imino group has a carbamate protecting group (COOR 0 The compound is protected by a carbamate protecting group (or a compound in which the secondary amino group of a cyclic amino acid is protected by a carbamate protecting group). Examples of the imino acid include proline, 3-pyrrolidinecarboxylic acid, 2-piperidinecarboxylic acid, 4-piperidinecarboxylic acid, and (4-piperidinyl)acetic acid.
[0068] Among the carbamate protecting groups, t-butoxycarbonyl group (Boc), benzyloxycarbonyl group (CBZ), and 9-fluorenylmethyloxycarbonyl group (Fmoc) are particularly preferred because they can be deprotected under mild conditions.
[0069] The cellulose (1-1) used in step [1] can preferably be wood pulp (coniferous pulp, hardwood pulp), cellulose derived from cotton linter pulp, crystalline cellulose, etc. These can be used individually or in combination of two or more. The pulp may contain other components such as hemicellulose. It is preferable to use the pulp in a finely crushed state, for example, by crushing it.
[0070] The reaction between cellulose (1-1) and imino acid (2) is preferably carried out in the presence of a catalyst. Examples of the catalyst include triethylamine, pyridine, and N,N-dimethyl-4-aminopyridine (DMAP). These can be used individually or in combination of two or more.
[0071] The amount of catalyst used is, for example, about 0.01 to 1.0 mole per mole of imino acid (2).
[0072] Furthermore, the reaction is preferably carried out in the presence of a condensing agent. Examples of the condensing agent include 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC-HCl), N,N'-dicyclohexylcarbodiimide, and N,N'-diisopropylcarbodiimide. These can be used individually or in combination of two or more.
[0073] The amount of the condensing agent used is, for example, about 0.01 to 1.0 mole per mole of imino acid (2).
[0074] The above reaction is preferably carried out in the presence of a solvent. Examples of the solvent include aliphatic hydrocarbons such as hexane, heptane, and octane; alicyclic hydrocarbons such as cyclohexane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; halogenated hydrocarbons such as chloroform, dichloromethane, and 1,2-dichloroethane; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and dioxane; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile, propionitrile, and benzonitrile; alcohols such as methanol, ethanol, isopropyl alcohol, and butanol; and dimethyl sulfoxides. These can be used individually or in combination of two or more.
[0075] Among the aforementioned solvents, amides such as N,N-dimethylacetamide are preferred, and using a mixture of the solvent and a lithium salt such as lithium chloride is particularly preferred in terms of its excellent solubility of cellulose. The concentration of the lithium salt in the solvent can be appropriately adjusted within a range that does not impair the effect of dissolving cellulose, for example, to about 1 to 30% by weight.
[0076] The amount of solvent used is, for example, about 0.5 to 30 times the total weight of the reaction substrate. If the amount of solvent used exceeds this range, the concentration of the reaction components tends to decrease, and the reaction rate tends to slow down.
[0077] After step [1], a cellulose derivative (II) having repeating units represented by the above formula (II) is produced.
[0078] Step [2] is a deprotection step of the imino group of the cellulose derivative (II) produced in step [1] (more specifically, a step of removing the protecting group of the imino group at the group represented by formula (b) that was introduced into the cellulose derivative (II)).
[0079] After step [2], a cellulose derivative (III) having repeating units represented by the above formula (III) is produced.
[0080] The method for removing the protecting group from the imino group of the cellulose derivative (II) can be appropriately selected depending on the type of protecting group.
[0081] For example, if a protecting group such as Boc is present, the protecting group can be removed by reacting it with a strong acid such as hydrochloric acid or trifluoroacetic acid. When cellulose derivative (III) is deprotected using a strong acid, the group represented by formula (c) may form a salt with a counteranion. For example, when trifluoroacetic acid is reacted as the strong acid, the terminal imino group of the group represented by formula (c) is CF3COO - and form a salt, ">N + H2·CF3COO - This can sometimes happen.
[0082] For example, if a protecting group is CBZ, the protecting group can be removed by carrying out a reduction reaction in the presence of a catalyst (e.g., Pd-C).
[0083] For example, if the protecting group is Fmoc, the protecting group can be removed by reacting it with a secondary amine such as pyridine.
[0084] The reaction temperature in step [2] is, for example, around 0 to 100°C. The reaction time is, for example, around 1 to 24 hours. After the reaction is complete, the reaction product obtained can be separated and purified by separation methods such as filtration, concentration, distillation, extraction, crystallization, adsorption, recrystallization, column chromatography, or a combination thereof.
[0085] Step [3] is a step in which the cellulose derivative (III) produced in step [2] is reacted with a quaternary ammonium compound represented by formula (3) in the presence of a sulfur compound.
[0086] R in equation (3)2 This is R in equation (a) above. 2 This corresponds to X in equation (3). - This indicates a counter anion, for example, OH - Cl - , Br - , I - F - SO4 2- BH4 - BF4 - PF6 - These are some examples.
[0087] Examples of the quaternary ammonium compounds include tetramethylammonium hydroxide and tetraethylammonium hydroxide.
[0088] The amount of the quaternary ammonium compound used is, for example, 50 parts by weight or more per 100 parts by weight of the cellulose derivative (III).
[0089] Examples of the sulfur compound include carbon disulfide. The amount of sulfur compound used is, for example, 20 parts by weight or more per 100 parts by weight of the cellulose derivative (III).
[0090] The reaction in step [3] is preferably carried out in the presence of a solvent. Examples of the solvent include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; alcohols such as methanol, ethanol, 2-propanol, isopropyl alcohol, and butanol; and N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide. These can be used individually or in combination of two or more. The amount of solvent used is, for example, about 0.5 to 30 times the total amount of the reaction substrate.
[0091] The reaction temperature in step [3] is, for example, around 0 to 100°C. The reaction time is, for example, around 1 to 24 hours. After the reaction is complete, the reaction product obtained can be separated and purified by separation methods such as filtration, concentration, distillation, extraction, crystallization, adsorption, recrystallization, column chromatography, or a combination thereof.
[0092] (B component) Component B is a coagulant. The coagulant neutralizes the surface charge of component A and suppresses the repulsion between components A. By adding component B to component A, the repulsion between components A is suppressed, making it easier to form flocs.
[0093] The cellulose derivative (I) contained in component A has a group represented by formula (a). Therefore, the surface of component A has an anionic charge. Accordingly, it is preferable to use a cationic coagulant (= cationic flocculant) as component B.
[0094] The aforementioned coagulants include inorganic coagulants and organic coagulants. These can be used individually or in combination of two or more.
[0095] Examples of the inorganic coagulants include aluminum-based flocculants such as aluminum sulfate, aluminum chloride, and polyaluminum chloride; and iron-based flocculants such as ferric chloride, ferrous chloride, and polyferric sulfate.
[0096] Examples of the organic coagulant include alkylamino (meth)acrylates, vinylamine compounds, allylamine compounds, condensed amine compounds, polyethyleneimines, and dicyandiamide compounds.
[0097] The weight-average molecular weight of the aforementioned organic coagulant is, for example, 1 × 10⁻⁶ 6 The following is preferably 1 × 10 5 More preferably 1 × 10 4 The following is particularly preferred: 0.5 × 10 4 The following is most preferably 1 × 10 3 The following applies:
[0098] The (meth)acrylate alkylamino ester is, for example, a polymer having monomer units derived from a monomer represented by the following formula (b). [ka]
[0099] In formula (b), L 1 The axine atom or NR group represents an oxygen atom or an NR group, and the R represents a hydrogen atom or an alkyl group. The alkyl group is, for example, an alkyl group having 1 to 10 carbon atoms (preferably 1 to 5, particularly preferably 1 to 3).
[0100] In formula (b), L 2 R represents an alkylene group with 1 to 4 carbon atoms. b1 ~R b3 R represents a hydrogen atom or a hydrocarbon group, either identical or different. b4 represents a hydrogen atom or a methyl group. - This indicates the paired anion.
[0101] Examples of the C1-C4 alkylene group include linear or branched alkylene groups such as methylene group, methylmethylene group, dimethylene group, propylene group, and trimethylene group. Among these, alkylene groups having C2-C4 are preferred, and alkylene groups having C2-C3 are particularly preferred.
[0102] The hydrocarbon groups include aliphatic hydrocarbon groups, alicyclic hydrocarbon groups, aromatic hydrocarbon groups, and groups formed by combining these. Among these, aliphatic hydrocarbon groups or aromatic hydrocarbon groups are preferred, and aliphatic hydrocarbon groups are particularly preferred.
[0103] As the aliphatic hydrocarbon group, alkyl groups having 1 to 10 carbon atoms (preferably 1 to 5, particularly preferably 1 to 3), such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, s-butyl, t-butyl, pentyl, and hexyl groups, are preferred.
[0104] Examples of the aforementioned counter anions include halogen anions and sulfate anions.
[0105] Examples of monomers that form the monomer unit represented by formula (b) include dialkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and dimethylamino-2-hydroxypropyl (meth)acrylate, as well as dialkylaminoalkyl (meth)acrylamides such as dimethylaminopropyl (meth)acrylamide, including hydrochloride salts, sulfates, methyl chloride adducts, benzyl chloride adducts, and dimethyl sulfate adducts.
[0106] The alkylamino (meth)acrylate may have other monomer units in addition to the monomer unit represented by formula (b) above. Examples of other monomer units include nonionic monomer units and anionic monomer units.
[0107] Examples of monomers that form the aforementioned nonionic monomer units (=nonionic monomers) include (meth)acrylamide, N,N'-di(alkyl)acrylamide, (meth)acrylic acid esters (e.g., methyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc.), vinyl esters (e.g., vinyl acetate, styrene, etc.), acrylonitrile, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, acryloylmorpholine, and the like.
[0108] Examples of monomers that form the anionic monomer units (= anionic monomers) include (meth)acrylic acid, maleic acid, itaconic acid, 2-acrylamido-2-methylsulfonic acid, and salts thereof (e.g., ammonium salts, sodium salts, potassium salts, etc.).
[0109] The proportion of monomer units represented by formula (b) in the total amount of monomer units constituting the alkylamino (meth)acrylate is, for example, 10 mol% or more, preferably 30 mol% or more, particularly preferably 50 mol% or more, and most preferably 70 mol% or more.
[0110] The (meth)acrylate alkylamino ester can be produced by polymerizing one monomer or copolymerizing two or more monomers.
[0111] Examples of the vinylamine compound include polymers of one monomer selected from N-vinyl carboxylic acid amide, N-vinyl formamide, N-vinyl acetamide, etc., and copolymers of two or more monomers.
[0112] Examples of the allylamine compounds include allylamine, diallylmethylamine, and salts thereof, or (co)polymers of monomers such as diallyldimethylammonium chloride.
[0113] Examples of the aforementioned condensed amine compounds include condensates of epichlorohydrin with at least one amine selected from monomethylamine, dimethylamine, monoethylamine, diethylamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, etc., and compounds obtained by further condensing the aforementioned condensates with polyamines such as ethylenediamine, diethylenetriamine, triethylenetetramine, and hexamethylenediamine.
[0114] Examples of the aforementioned dicyandiamide compounds include dicyandiamide / formaldehyde condensates and dicyandiamide / formaldehyde / ammonium chloride condensates.
[0115] (C component) The aforementioned component C is a polymer flocculant. The polymer flocculant flocces component A, whose surface charge has been neutralized by the addition of component B. The component A flocculated by the polymer flocculant forms flocs in the liquid and precipitates.
[0116] The aforementioned polymer flocculants include anionic polymer flocculants, cationic polymer flocculants, amphoteric polymer flocculants, and nonionic polymer flocculants. These can be used individually or in combination of two or more.
[0117] The weight-average molecular weight of the aforementioned polymer flocculant is, for example, 2 × 10⁻⁶ 6 Preferably 3 × 10 6 In particular, 4 × 10 6 In summary, 5 × 10 is most preferable. 6 That concludes the explanation. The upper limit of the weight-average molecular weight is, for example, 50 × 10 6 Preferably 20 × 10 6 Preferably 18 × 10 6 Therefore, if a polymer flocculant with a weight-average molecular weight within the aforementioned range is used, flocs can be formed quickly.
[0118] The form of the polymer flocculant is not particularly limited, and any form such as aqueous solution, dispersion, emulsion, or powder can be used.
[0119] <Anionic polymer flocculant> The anionic polymer flocculant is a polymer having monomer units derived from anionic monomers. The proportion of monomer units derived from the anionic monomers in the total monomer units constituting the polymer is, for example, 10% by weight or more, preferably 30% by weight or more, more preferably 50% by weight or more, particularly preferably 70% by weight or more, and most preferably 90% by weight or more.
[0120] The anionic polymer flocculant may contain monomer units other than those derived from anionic monomers. Examples of other monomer units include monomer units derived from nonionic monomers.
[0121] Examples of the anionic monomer and nonionic monomer are the same as those described in the section on component B.
[0122] The aforementioned anionic polymer flocculant can be produced by (co)polymerizing an anionic monomer with other monomers as needed (for example, aqueous solution polymerization, water-in-oil emulsion polymerization, or water-in-oil dispersion polymerization).
[0123] <Cationic polymer flocculant> The cationic polymer flocculant is a polymer having monomer units derived from cationic monomers. The proportion of monomer units derived from cationic monomers in the total monomer units constituting the polymer is, for example, greater than 0% by weight and 100% by weight or less. The lower limit of the proportion is preferably 1% by weight, and particularly preferably 5% by weight. The upper limit of the proportion is preferably 90% by weight, more preferably 70% by weight, particularly preferably 50% by weight, and most preferably 30% by weight.
[0124] The cationic polymer flocculant may contain monomer units other than those derived from cationic monomers. Examples of other monomer units include monomer units derived from anionic monomers and monomer units derived from nonionic monomers.
[0125] Examples of the cationic monomer include the monomer represented by formula (b) described in the section on component B. Examples of the anionic monomer and nonionic monomer are the same as those described in the section on component B.
[0126] The cationic polymer flocculant can be produced by (co)polymerizing a cationic monomer with other monomers as needed.
[0127] <Amphoteric polymer flocculant> The aforementioned amphoteric polymer flocculant is a polymer having monomer units derived from cationic monomers and monomer units derived from anionic monomers. The weight ratio (former / latter) of monomer units derived from cationic monomers to monomer units derived from anionic monomers is, for example, 40 / 60 to 60 / 40.
[0128] The proportion of the total monomer units derived from cationic monomers and monomer units derived from anionic monomers in the total monomer units constituting the polymer is, for example, 10% by weight or more, preferably 30% by weight or more, more preferably 50% by weight or more, particularly preferably 70% by weight or more, and most preferably 90% by weight or more.
[0129] The aforementioned amphoteric polymer flocculant may contain other monomer units in addition to monomer units derived from cationic monomers and monomer units derived from anionic monomers. Examples of other monomer units include monomer units derived from nonionic monomers.
[0130] Examples of the nonionic monomer can be the same as those described in the section on component B.
[0131] The aforementioned amphoteric polymer flocculant can be produced by copolymerizing a cationic monomer, an anionic monomer, and other monomers as needed.
[0132] <Nonionic polymer flocculant> The aforementioned amphoteric polymer flocculant is a polymer or copolymer of nonionic monomers.
[0133] Examples of the nonionic monomer can be the same as those described in the section on component B.
[0134] The aforementioned amphoteric polymer flocculant can be produced by polymerizing one nonionic monomer or copolymerizing two or more nonionic monomers.
[0135] Among the C components, the use of an anionic polymer flocculant is preferable because it allows for rapid floc formation and efficient metal fixation. Furthermore, among anionic polymer flocculants, the use of a polymer in which monomer units derived from anionic monomers account for 30% by weight or more (preferably 50% by weight or more, particularly preferably 70% by weight or more, and most preferably 90% by weight or more) is preferable because it allows for rapid floc formation and the formation of large flocs, making separation from the liquid particularly easy.
[0136] The proportion of the anionic polymer flocculant in the total amount of component C is, for example, 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, particularly preferably 80% by weight or more, and most preferably 90% by weight or more.
[0137] [Metal fixing method] The metal fixation method of this disclosure comprises the steps of adding component A to an aqueous solution containing a dissolved metal, and then adding component B and component C to form a floc containing the metal, component A, component B, and component C.
[0138] The metal exists as a metal ion in the aqueous solution. When component A is added to the aqueous solution, the metal ions adsorb to component A by forming a chelate complex with the group represented by formula (a) of the cellulose derivative (I), which is component A.
[0139] The amount of component A used is, for example, 200 to 3000 g, preferably 200 to 2000 g, and particularly preferably 200 to 1000 g, per mole of metal contained in the aqueous solution.
[0140] To promote the adsorption of metal ions onto component A, it is preferable to stir and / or shake the aqueous solution for, for example, 1 minute to 1 hour after adding component A to the aqueous solution.
[0141] Furthermore, adjusting the pH of the aqueous solution to, for example, 1 to 9 (particularly 1 to 7, and especially 2 to 6) is preferable because it can further improve the adsorption of metal ions to component A. Note that the pH of the aqueous solution can be adjusted using well-known and conventional pH adjusting agents (acids such as nitric acid, or alkalis such as sodium hydroxide).
[0142] After adsorbing metal ions onto component A in an aqueous solution, components B and C are added to the solution. Components B and C may be added simultaneously, or component B may be added first, followed by component C.
[0143] To promote floc formation, it is preferable to stir and / or shake the aqueous solution for about 30 minutes to 2 hours after adding components B and C to the aqueous solution.
[0144] The amount of component B used is, for example, 0.1 to 10 parts by weight, preferably 0.1 to 5 parts by weight, particularly preferably 0.1 to 3 parts by weight, and most preferably 0.1 to 2.0 parts by weight, per 1 part by weight of component A. By using component B within the above range, the repulsion between components A can be suppressed, and the effect of promoting floc formation can be obtained.
[0145] The amount of component C used is, for example, 0.1 to 10 parts by weight, preferably 0.1 to 5 parts by weight, particularly preferably 0.1 to 2 parts by weight, and most preferably 0.1 to 1.5 parts by weight, per 1 part by weight of component A. By using component C within this range, the A components whose surface charge has been neutralized by component B can be aggregated, and flocs can be rapidly formed.
[0146] The ratio of the amounts of component B to component C used (B / C; weight ratio) is, for example, 20 / 80 to 80 / 20, preferably 30 / 70 to 80 / 20, particularly preferably 40 / 60 to 75 / 25, most preferably 50 / 50 to 75 / 25, and especially preferably 55 / 45 to 75 / 25.
[0147] The flocs formed in the aqueous solution in this manner can be separated from the aqueous solution by simple methods such as filtration. Furthermore, the separated flocs can be reduced in volume by heat treatment. The volume reduction rate is, for example, 90% or more, preferably 95% or more. Additionally, the metal fixed within the flocs can be recovered by burning them.
[0148] The configurations and combinations thereof described above are examples only, and additions, omissions, substitutions, and modifications to the configurations may be made as appropriate, without departing from the spirit of this disclosure. [Examples]
[0149] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited by these examples, but is limited only by the claims.
[0150] Preparation Example 1 (Preparation of Cellulose Derivatives) Cellulose (1-1) (0.501 g, 3.08 mmol) was placed in a two-necked round-bottom flask and vacuum-dried at 90°C for 2 hours. Under a nitrogen atmosphere, N,N-dimethylacetamide (15 mL) and lithium chloride (0.99 g) were added to dissolve the cellulose. N,N-dimethyl-4-aminopyridine (2.26 g, 18.5 mmol), N-Boc-L-proline (3.98 g, 18.5 mmol), 1-ethyl 3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) (3.55 g, 18.5 mmol), and N,N-dimethylacetamide (15 mL) were added to this reaction vessel, and the mixture was stirred at room temperature for 24 hours. The reaction mixture was poured into water and reprecipitation was performed, and the resulting solid was collected by suction filtration. The obtained solid was dissolved in ethanol, reprecipitation was performed with water, and the solid was collected by suction filtration. The solid was vacuum-dried to obtain DMC-Pro-II (1.81 g, yield 78%), represented by the following formula, as a white solid. 1 Based on the results of the 1H-NMR measurement, the overall average degree of substitution of N-Boc-proline was calculated to be 3.0.
[0151] [ka] (DMC-Pro-II) 1 H-NMR (500 MHz, CDCl3,55℃):δ4.00-5.30 (br, 8H), 2.95-4.00 (br, 8H), 1.60-2.56 (br, 12H), 1.43 (br, 27H)
[0152] Under a nitrogen atmosphere, trifluoroacetic acid (6.6 mL) and DMC-Pro-II (1.00 g, 1.33 mmol) were added to a two-necked round-bottom flask and stirred at room temperature for 7.5 hours. The precipitated solid was recovered by centrifugation after reprecipitation with diethyl ether and washed with diethyl ether. The obtained solid was vacuum-dried to obtain a salt of DMC-Pro-III represented by the following formula as a white solid (979 mg, yield 92%). 1 The results of the H-NMR measurement are shown below.
[0153] [ka] (DMC-Pro-III) 1 H-NMR (500 MHz, D2O, rt):δ 5.24 (br, 1H), 4.91 (br, 1H), 4.80 (br, overlapped with HDO), 4.45 (br, 3H), 4.21 (br, 1H), 4.06 (br, 1H), 3.81 (br, 1H), 3.67 (br, 1H), 3.32(br, 6H), 2.18-2.54 (br, 3H), 1.60-2.16 (br, 9H)
[0154] Under a nitrogen atmosphere, 0.500 g, 0.628 mmol of DMC-Pro-III salt was dissolved in 3.1 mL of dimethyl sulfoxide in a two-necked round-bottom flask, and carbon disulfide (0.57 mL, 9.4 mmol) was added. The mixture was cooled to approximately 10°C under light shielding, and 3.77 mL, 3.77 mmol of 10% tetramethylammonium hydroxide methanol solution was added dropwise. The mixture was stirred for 7 hours while increasing the temperature to room temperature. The solid obtained by reprecipitation in ethanol was recovered by centrifugation and washed with ethanol. The obtained solid was vacuum-dried to obtain cellulose derivative 1 (DMC-Pro, weight-average molecular weight: approximately 100,000), represented by the following formula, as a white solid (453 mg, yield 80%). The IR spectrum of cellulose derivative 1 (DMC-Pro) is shown in Figure 1.
[0155] [ka] (DMC-Pro) 1 H-NMR (500 MHz, D2O, rt):δ 4.40-5.70 (br, overlapped with HDO), 3.35-4.40 (br), 3.15 (br,CH3), 1.20-2.85 (br)
[0156] Examples 1-9 20 mg of cellulose derivative 1 and 10 mL of 2.0 mM As(III) aqueous solution (initial concentration of As(III): B μmol / L) were added to a 50 mL polyethylene centrifuge tube, and the mixture was shaken at 200 rpm, 25 °C, and 20 minutes. Subsequently, 20 mg of a coagulant (CHP295) and 10 mg of a polymer flocculant (component C listed in Table 1 below) were added, and the mixture was shaken again for 1 hour. The reaction mixture, after shaking, was centrifuged (3000 rpm, 25°C, 30 minutes) and filtered through a syringe filter with a pore size of 0.45 μm. The obtained filtrate was subjected to ICP-AES analysis to quantify the As(III) concentration (Sμmol / L) in the filtrate, and the amount of As(III) fixed per unit volume of component C was calculated using the following formula. As(III) fixed amount (μmol / g) = [(BS)×10 / 1000] / C component usage amount (g)
[0157] Comparative Examples 1-9 The procedure was carried out in the same manner as in Examples 1 to 9, except that cellulose derivative 1 was not used and component C listed in Table 1 below was used as the polymer flocculant.
[0158] The results are summarized in Table 1 below. [Table 1]
[0159] Table 1 shows that the amount of As(III) adsorbed is significantly improved when cellulose derivative 1 is used in combination with the coagulant and polymer flocculant.
[0160] Examples 10-13 20 mg of cellulose derivative 1 and 10 mL of 2.0 mM As(III) aqueous solution were added to a 50 mL centrifuge tube, and the tube was shaken using a shaker (BR-30L; Taitec, Aichi) at 200 rpm, 25°C, and for 20 minutes. Subsequently, 20 mg of a coagulant (CHP295) was added, and the mixture was shaken at 200 rpm and 25°C for 2 minutes. Next, 10 mg of the polymer flocculant (component C listed in Table 2 below) was added, and the mixture was shaken at 200 rpm and 25°C for 5 minutes. The time (in seconds) required for floc formation after shaking the sample and allowing it to stand was measured to evaluate its floc-forming ability.
[0161] The results are summarized in Table 2 below. [Table 2]
[0162] Table 2 shows that the floc formation rate is faster when anionic polymer flocculants are used, and in particular, the floc formation rate is faster when anionic polymer flocculants with a high proportion of anionic monomers are used.
[0163] (Considering the influence of other metals) For aqueous solutions containing 12 metal elements (Mg, Ca, Sr, Ba, Cu, Mn, Co, Ni, Zn, Pb, As, Se), the amount of fixation of each metal element was measured when component A (cellulose derivative 1) was used in combination with component B (CHP295) and component C (APP199), and when component A (cellulose derivative 1) was not used. The measurement method was the same as in Example 6, except that an aqueous solution containing 12 different metal elements was used instead of a 2.0 mM As(III) aqueous solution.
[0164] The results are summarized in Table 3 below. [Table 3]
[0165] Table 3 shows that even with the addition of component A, the fixation rate of alkaline earth metals, which are hard acids, was less than 80%, while valuable and hazardous metals, which are soft or intermediate acids, all showed high fixation rates of 97% or more. In particular, the fixation rates of As(III) and Se(IV) increased significantly with the addition of component A. From these results, it can be seen that the metal fixing material of this disclosure can efficiently fix valuable and hazardous metals.
[0166] Furthermore, the flocs obtained using cellulose derivative 1, a coagulant (CHP295), and a polymer flocculant (APP199) were dried for 3 days. The mass of the dried flocs was 19 mg. Subsequently, sintering was performed. The mass after sintering was 0.2 mg (volume reduction rate of 97%). From the above, it can be seen that using the metal fixing material of this disclosure makes it possible to significantly reduce the volume of flocs, and by reducing the volume of flocs, the cost of disposal can also be significantly reduced.
[0167] Comparative Examples 10, 11 As an adsorbent, except that N-700 or sodium N,N-diethyldithiocarbamate trihydrate (referred to as "monomer" in Table 4) was used instead of cellulose derivative 1, the amount of As(III) fixed was measured in the same manner as in Example 6.
[0168] The results are summarized in Table 4 below.
Table 4
[0169] From Table 4, it was found that when cellulose derivative 1 was used as the adsorbent, more As(III) could be immobilized than when low-molecular-weight compounds or monomers were used.
[0170] The compounds used in the examples and comparative examples are described below. <Component A> Cellulose derivative 1 (prepared in Preparation Example 1) <Component B> CHP295 (cationic flocculant, weight-average molecular weight: 1×10 [[ID=2?]] 6 hereinafter, cationic monomer ratio: 100%), manufactured by Mitsubishi Chemical Corporation <Component C> Anionic polymer flocculant AP199, anionic monomer ratio: 100%, weight-average molecular weight: 5×10 6 , manufactured by Mitsubishi Chemical Corporation AP120CH, anionic monomer ratio: 20%, weight-average molecular weight: 13×10 6 , manufactured by Mitsubishi Chemical Corporation Cationic polymer flocculant KP201C, cationic monomer ratio: 100%, weight-average molecular weight: 2×10 6 above, manufactured by Mitsubishi Chemical Corporation KP1200B, cationic monomer ratio: 80%, weight-average molecular weight: 2×10 6 above, manufactured by Mitsubishi Chemical Corporation KP1201B, cationic monomer ratio: 60%, weight-average molecular weight: 2×10 6The above is manufactured by Mitsubishi Chemical Corporation. KP204B, cationic monomer content: 40%, weight-average molecular weight: 14 × 10 6 , manufactured by Mitsubishi Chemical Corporation KP206B, cationic monomer content: 20%, weight-average molecular weight: 14 × 10⁻⁶ 6 , manufactured by Mitsubishi Chemical Corporation Nonionic polymer flocculant NP500, weight average molecular weight: 16×10 6 , manufactured by Mitsubishi Chemical Corporation Amphoteric polymer flocculant KA405D, weight average molecular weight: 8×10 6 , manufactured by Mitsubishi Chemical Corporation <Other> Sodium N,N-diethyldithiocarbamate trihydrate, manufactured by Wako Pure Chemical Industries, Ltd. N-700, a water-soluble dithiocarbamate-containing metal immobilizing agent, weight-average molecular weight: 0.1 × 10⁻⁶ 6 The following is the product name "Nitto Guard," manufactured by Mitsubishi Chemical Corporation.
[0171] The following metal elements were used: 1000 mg / L arsenic standard solution, calcium standard solution, magnesium standard solution, manganese standard solution, zinc standard solution, barium standard solution, cobalt standard solution, selenium standard solution, strontium standard solution, lead standard solution (1000 mg / L, for atomic absorption spectrometry, Kanto Chemical), copper standard solution, and nickel standard solution (1000 mg / L, for research and testing).
[0172] For solution preparation, purified water produced using an ultrapure water production system (Arium pro UV, Sartorius), nitric acid (for heavy metal measurement; Kanto Chemical), hydrochloric acid (for arsenic measurement; Kanto Chemical), sodium hydroxide (special grade; Kanto Chemical), and as buffering agents, Good's buffers 2-(N-monophorino)-ethanesulfonic acid (special grade; Sigma-Aldrich), 4-(2-hydroxyethyl)-piperazineethanesulfonic acid (special grade; Nacalai Tesque), 3-[N-tris(hydroxymethyl)methyl-3-amino]-1-propanesulfonic acid (special grade; MP Biomedicals), and 3-cyclohexylaminopropanesulfonic acid were used.
[0173] For measuring metal concentrations, an inductively coupled plasma emission spectrometer (iCAP 6300, Thermo Fisher) was used.
Claims
1. A metal fixing material comprising a combination of the following components A, B, and C. Component A: a metal adsorbent containing a cellulose derivative having a repeating unit represented by the following formula (I): 【Chemistry 1】 [In the formula, R a are the same or different and are a hydrogen atom or a group represented by the following formula (a): a at least one of which is a group represented by the following formula (a): 【Chemistry 2】 (wherein ring Z represents a heterocycle containing a nitrogen atom as a heteroatom, R 1 represents a single bond or an alkylene group having 1 to 10 carbon atoms. 2 are the same or different and represent alkyl groups having 1 to 10 carbon atoms. Component B: Coagulant Component C: Polymer flocculant
2. The metal fixing material of claim 1 , wherein the coagulant is a cationic coagulant.
3. The metal fixing material according to claim 1 or 2, wherein the polymer flocculant is an anionic polymer flocculant.
4. The metal fixing material described in claim 3, wherein the anionic polymer flocculant is a polymer containing monomer units derived from anionic monomers, and the proportion of the monomer units derived from the anionic monomers in the total monomer units constituting the polymer is 30% by weight or more.
5. The metal fixing material according to any one of claims 1 to 4, wherein the component B is contained in an amount of 0.1 to 10 parts by weight per 1 part by weight of the component A.
6. The metal fixing material according to any one of claims 1 to 5, wherein the component C is contained in an amount of 0.1 to 10 parts by weight per 1 part by weight of the component A.
7. The metal fixing material according to any one of claims 1 to 6, wherein the ratio of the contents of the B component and the C component (B / C; weight ratio) is 20 / 80 to 80 / 20.
8. The metal fixing material according to any one of claims 1 to 7, wherein the metal fixing material is a fixing material of the following metals: Metal: A metal whose cation is a soft acid or intermediate acid according to the HSAB rule.
9. The metal fixing material according to any one of claims 1 to 7, wherein the metal fixing material is a fixing material of at least one metal selected from titanium, vanadium, manganese, iron, cobalt, nickel, copper, zinc, gallium, arsenic, selenium, cadmium, indium, lead, bismuth, ruthenium, rhodium, iridium, palladium, platinum, silver, and gold.
10. A method for fixing a metal, comprising the steps of adding the following component A to an aqueous solution containing a dissolved metal, and then adding the following components B and C to form flocs containing the metal, component A, component B, and component C. Component A: a metal adsorbent containing a cellulose derivative having a repeating unit represented by the following formula (I): 【Transformation 3】 [In the formula, R a are the same or different and are a hydrogen atom or a group represented by the following formula (a): a at least one of which is a group represented by the following formula (a): 【Chemistry 4】 (wherein ring Z represents a heterocycle containing a nitrogen atom as a heteroatom, R 1 represents a single bond or an alkylene group having 1 to 10 carbon atoms. 2 are the same or different and represent alkyl groups having 1 to 10 carbon atoms. Component B: Coagulant Component C: Polymer flocculant